El marketing digital como estrategia para el crecimiento de ventas en la microempresa muebles Barahona, cantón Riobamba, período 2017. - Barahona Armijo, Fanny Valeria (2017)
The present research work was carried out in the period 2017 in the Barahona Furniture Microenterprise, the microenterprise has a trajectory of 37 years in the market. Their sales have been decreed, no digital technological means have been used to promote themselves; that is why the need arises to determine a Digital Marketing strategy for the microenterprise that influences the growth of sales. A population base of 379 families of the city of Riobamba was made, considering the five parishes: Lizarzaburu, Veloz, Maldonado, Velasco and Yaruquíes. The investigation was framed in the inductive method of correlation type and field with a non experimental design. Techniques and instruments such as the survey were used; to evaluate if the families of the city of Riobamba use digital technological means to visualize, compare prices, characteristics and models of different types of furniture and buy means through said means, the unstructured interview; It was necessary to determine if the administration used digital technological means and the predisposition to use; After tabulating and analyzing data, it was generally determined that families want micro-businesses in the city to have web pages and an attractive digital corporate image for buyers. Thanks to the support of the Wix tool for its design, the creation of a virtual store was important as a marketing strategy, which was complemented with the promotion through Facebook.